Influence of the Environment on al-Layth bin Sa’d´s School of Islamic Law - Tlili, Vaclava (Ulumuna, 2024)
The aim of this study is to bring back to the light one of the forgotten Islamic jurist al-Layth bin Sa‘d, and find out how the environment may have influenced his legal reasoning. The first part focuses on the influence of a specific environment on human thinking in general and points to the factors influencing the formation of Islamic law in various areas in paticular. The rest of the paper discusses Layth ibn Sa‘d´s personality and the elements that may have contributed to his conception of legal thought; the very multi-religious nature of early Islamic Egypt has been identified as one of the significant elements that helped shape the central nature of his legal school. The conclusion of the study provides examples of some legal rulings issued by him, in which the key role of his environment is clearly demonstrated, and the different legal approach of other lawyers is pointed out.